Etrolizumab versus infliximab for the treatment of moderately to severely active ulcerative colitis (GARDENIA): a randomised, double-blind, double-dummy, phase 3 study. (February 2022) - Danese, Silvio; Colombel, Jean-Frederic; Lukas, Milan; Gisbert, Javier P; D'Haens, Geert; Hayee, Bu'hussain; Panaccione, Remo; Kim, Hyun-Soo; Reinisch, Walter; Tyrrell, Helen; Oh, Young S; Tole, Swati; et al.
Summary: Background: Etrolizumab is a gut-targeted anti-β7 integrin monoclonal antibody. In a previous phase 2 induction study, etrolizumab significantly improved clinical remission versus placebo in patients with moderately to severely active ulcerative colitis. We aimed to compare the safety and efficacy of etrolizumab with infliximab in patients with moderately to severely active ulcerative colitis. Methods: We conducted a randomised, double-blind, double-dummy, parallel-group, phase 3 study (GARDENIA) across 114 treatment centres worldwide. We included adults (age 18–80 years) with moderately to severely active ulcerative colitis (Mayo Clinic total score [MCS] of 6–12 with an endoscopic subscore of ≥2, a rectal bleeding subscore of ≥1, and a stool frequency subscore of ≥1) who were naive to tumour necrosis factor inhibitors. Patients were required to have had an established diagnosis of ulcerative colitis for at least 3 months, corroborated by both clinical and endoscopic evidence, and evidence of disease extending at least 20 cm from the anal verge. Participants were randomly assigned (1:1) to receive subcutaneous etrolizumab 105 mg once every 4 weeks or intravenous infliximab 5 mg/kg at 0, 2, and 6 weeks and every 8 weeks thereafter for 52 weeks. Randomisation was stratified by baseline concomitant treatment with corticosteroids, concomitant treatment with immunosuppressants, and baseline disease activity. All participants and study site personnel were masked to treatment assignment. The primary endpoint was the proportion of patients who had both clinical response at week 10 (MCS ≥3-point decrease and ≥30% reduction from baseline, plus ≥1-point decrease in rectal bleeding subscore or absolute rectal bleeding score of 0 or 1) and clinical remission at week 54 (MCS ≤2, with individual subscores ≤1); efficacy was analysed using a modified intention-to-treat population (all randomised patients who received at least one dose of study drug). GARDENIA was designed to show superiority of etrolizumab over infliximab for the primary endpoint. This trial is registered with ClinicalTrials.gov, NCT02136069, and is now closed to recruitment. Findings: Between Dec 24, 2014, and June 23, 2020, 730 patients were screened for eligibility and 397 were enrolled and randomly assigned to etrolizumab (n=199) or infliximab (n=198). 95 (48%) patients in the etrolizumab group and 103 (52%) in the infliximab group completed the study through week 54. At week 54, 37 (18·6%) of 199 patients in the etrolizumab group and 39 (19·7%) of 198 in the infliximab group met the primary endpoint (adjusted treatment difference –0·9% [95% CI –8·7 to 6·8]; p=0·81). The number of patients reporting one or more adverse events was similar between treatment groups (154 [77%] of 199 in the etrolizumab group and 151 [76%] of 198 in the infliximab group); the most common adverse event in both groups was ulcerative colitis (55 [28%] patients in the etrolizumab group and 43 [22%] in the infliximab group). More patients in the etrolizumab group reported serious adverse events (including serious infections) than did those in the infliximab group (32 [16%] vs 20 [10%]); the most common serious adverse event was ulcerative colitis (12 [6%] and 11 [6%]). There was one death during follow-up, in the infliximab group due to a pulmonary embolism, which was not considered to be related to study treatment. Interpretation: To our knowledge, this trial is the first phase 3 maintenance study in moderately to severely active ulcerative colitis to use infliximab as an active comparator. Although the study did not show statistical superiority for the primary endpoint, etrolizumab performed similarly to infliximab from a clinical viewpoint. Funding: F Hoffmann-La Roche.